Da'wah "Islam Nusantara" on NU Online and the Surrounding Argue - Ghulam, Zainil; Farid, Achmad; Ghofur, Abdul (Dakwah, 2024)
This article discusses the propagation and narrative of "Islam Nusantara" conveyed by NU Online, as a social media managed by the Nahdlatul Ulama or NU Executive Board. The NU Online channel has a number of platforms, including websites, Instagram, Twitter, TikTok and YouTube. This study discusses how the implementation of Indonesian Islamic da'wah on NU social media. This study uses a qualitative method with a digital discourse analysis approach. The results of this research show that, as an organization that claims to be moderate and aware of current developments, NU uses digital media to conduct da'wah. Social media is also used to counterattack and/or defend major religious narratives that have been spread in public spaces for a long time. The narrative in question is Islam Nusantara or a religious method based on moderation and pluralism in Indonesian society. In the current era of social media, debates about matters concerning Islam cannot be avoided. Therefore, each Islamic community group tries to carry out its activities while maintaining its ideology.